New Insights Into the Lineage-Specific Expansion and Functional Diversification of Lamprey AID/APOBEC Family - Chen, Yan; Luo, Lingjie; Deng, Lisi; Tian, Xiaoxue; Chen, Shangwu; Xu, Anlong; Yuan, Shaochun (Frontiers in Immunology, 2022)
The AID/APOBEC family which converts cytidine to uridine on RNA or DNA experienced dynamic expansion in primates in order to resist exogenous viruses and endogenous retrotransposons. Recently, expansion of AID/APOBEC-like homologs has also been observed in the extant jawless vertebrate lamprey. To reveal what causes such expansion and leads to the functional diversification of lamprey cytosine deaminases (CDAs), we reassessed the CDA genes in Lethenteron japonicum (Lj). We first confirmed the expansion of LjCDA1L1 (CDA1-like 1) genes and found the expression correlation of LjCDA2 and LjCDA1L2 with LjVLRs (variable lymphocyte receptors). Among up to 14 LjCDA1L1 proteins, LjCDA1L1_4a has an extremely high deamination activity on ssDNA and buDNA and, unexpectedly, on dsDNA. LjCDA1L1s can also restrict the infection of HSV-1 particles. Thus, the arms race between the host and pathogens along with the recruitment by VLR assembly may participate together to form a driving force in the expansion and diversification of the lamprey AID/APOBEC family.